2018
DOI: 10.1186/s12984-018-0394-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of robot-assisted gait training with dorsiflexion assistance on chronic stroke patients wearing ankle-foot-orthosis

Abstract: BackgroundRobot-assisted ankle-foot-orthosis (AFO) can provide immediate powered ankle assistance in post-stroke gait training. Our research team has developed a novel lightweight portable robot-assisted AFO which is capable of detecting walking intentions using sensor feedback of wearer’s gait pattern. This study aims to investigate the therapeutic effects of robot-assisted gait training with ankle dorsiflexion assistance.MethodsThis was a double-blinded randomized controlled trial. Nineteen chronic stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 48 publications
5
113
0
Order By: Relevance
“…An exoskeleton ankle robot has been developed and evaluated by our research team in a pilot randomized controlled trial (RCT) for chronic stroke subjects with foot drop problem. Our ndings showed chronic stroke subjects had signi cant improvement in gait independency and enhanced gait con dence at heel strike after 20-session gait training wearing this robot for stair and over-ground gait training [18]. Similar ankle rehabilitation robotics have also shown their potential to be an alternative gait rehabilitation for stroke [19][20][21][22][23], examples are Anklebot [8] and ReStore (ReWalk Robotics, USA) [24].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…An exoskeleton ankle robot has been developed and evaluated by our research team in a pilot randomized controlled trial (RCT) for chronic stroke subjects with foot drop problem. Our ndings showed chronic stroke subjects had signi cant improvement in gait independency and enhanced gait con dence at heel strike after 20-session gait training wearing this robot for stair and over-ground gait training [18]. Similar ankle rehabilitation robotics have also shown their potential to be an alternative gait rehabilitation for stroke [19][20][21][22][23], examples are Anklebot [8] and ReStore (ReWalk Robotics, USA) [24].…”
Section: Introductionmentioning
confidence: 75%
“…The robot weighted 0.5 kg (including AFO and motor) on the leg, with the control box (0.5 kg) held by the trainer. This robot had been evaluated in previous RCT which demonstrated greater functional improvement on chronic stroke [18]. The current RCT focused on evaluating its therapeutic effects on sub-acute stroke.…”
Section: Interventionmentioning
confidence: 99%
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 85%
“…A bending stiffness control was implemented on a flexible rigid AFO. The AFO was able to bend to a certain degree as such AFOs are made from a thermal plastic material such as polypropylene [18,57], and carbon fiber [19]. The works reported AFOs with different bending stiffness values such as 0.19 N·m [23] and 2.52 N·m [58].…”
Section: Bending Stiffness Controlmentioning
confidence: 99%
“…Then, on the third week, the user gait without the assistance of the AFO was analyzed. The effects of the provision of an AFO on rehabilitation was measured on an AFO with a bending stiffness control [57] in the short-term, long-term, and even in terms of the immediate effect (during the provision of the AFO) [16,19]. The immediate effects of an AFO with gait control, such as damping stiffness, assistive torque, and motion control, on the user have been reported, such as a higher walking speed, longer stride length, and so on [72], but without focusing on the short-term or long-term utilization [74,96].…”
Section: Controller Performance Evaluationmentioning
confidence: 99%